Performances of Disappearance: Ana Mendieta’s Work as Feminist-Decolonial Historiography? - Dias, Luciana da Costa (2025)
This paper examines the biography and work of Ana Mendieta (1948-1985), a Cuban-born artist exiled in the United States, through the lens of gender-based violence and historical memory in Latin America. The text highlights her early displacement during the Cuban Revolution – particularly after the Bay of Pigs incident (1961), which led to her father’s imprisonment and the separation from her family – as a foundational trauma that permeated her practice. Mendieta used performance art to explore the violence endured by women, especially racialized and migrant bodies, as seen in her iconic works like Rape Scene (1973) and the Silueta Series (1973-1980). Her oeuvre echoes broader concerns in Latin American feminist performance and rethinks how women artists negotiate history (and history of art). The work argues that Mendieta not only exposed historical colonial wounds, but transformed them into sites of poetic, feminist resistance.